Problems of the conceptual and terminological apparatus of the procedure for initiating forensic examination in criminal proceedings - A. V. Kovalenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the formulation of a stable conceptual and terminological apparatus of the procedure for initiating a forensic examination in criminal proceedings. The provisions of the current criminal procedural legislation regarding the procedures for initiating forensic examinations have been analyzed. It has been found that the specified procedures have at least nine different legally established names, which contradicts the requirements of the principle of legal certainty and may lead to confusion in practice.